Evidence of superparamagnetic behaviour in an amorphous Ni62Mn38 film by ESR measurements - (:unkn) unknown (ELSEVIER SCIENCE BV, 1998)
Electron spin resonance (ESR) measurements were carried out on an amorphous Ni62Mn38 film in the temperature range of 4-300 It. The spectra comprise multi-peak resonance absorptions forming mainly two groups separated in the magnetic field; one of which corresponds to unresolved usual spin-wave resonance (SWR) modes, the other occurs at about H = 3 kG for the applied field parallel to the film surface and shows a rather less dependence on the field direction compared to those of the main SWR modes. It has been observed that the latter peak becomes more and more apparent (the amplitude intensifies and the linewidth decreases) with decreasing temperature and then starts again to broaden as the temperature is further decreased. This overall behaviour leads us to suggest that the sample consists of a large number of smaller clusters coupled weakly to each other. Macroscopic ferromagnetic state averaged over all these clusters gives us the usual SWR peaks. However, each weakly coupled cluster behaves as an almost free individual magnetic entity and therefore the latter peak can be attributed to the superparamagnetic resonance absorbtions. By fitting the theoretical SWR modes simultaneously to the corresponding experimental ones for parallel and perpendicular geometries, the exchange stiffness constant D, the exchange unidirectional anisotropy field H-exe, the bulk magnetic anisotropy constant 2K(eff)/M-0 and the surface pinning parameter QL have been obtained as a function of temperature. The results have been compared with the existing data for the NiMn alloys with different compositions. The role of the local spin fluctuations (LSFs) on the temperature dependence of the magnetic parameters mentioned above has been discussed. (C) 1998 Elsevier Science B.V, All rights reserved.
Keywords: reentrant spin glass; magnetic anisotropy; spin wave resonance; amorphous thin films; REENTRANT SPIN-GLASSES; DISORDERED NI-MN; ALLOYS; RESONANCE; RESISTIVITY; ANISOTROPY; ANOMALIES